2018
DOI: 10.3389/fmicb.2018.01725
|View full text |Cite
|
Sign up to set email alerts
|

Chestnut Honey and Bacteriophage Application to Control Pseudomonas aeruginosa and Escherichia coli Biofilms: Evaluation in an ex vivo Wound Model

Abstract: Chronic skin wounds represent a major burn both economically and socially. Pseudomonas aeruginosa and Escherichia coli are among the most common colonizers of infected wounds and are prolific biofilm formers. Biofilms are a major problem in infections due to their increasingly difficult control and eradication, and tolerance to multiple prescribed drugs. As so, alternative methods are necessary. Bacteriophages (phages) and honey are both seen as a promising approach for biofilm related infections. Phages have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
46
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(51 citation statements)
references
References 70 publications
1
46
0
Order By: Relevance
“…In the case of biofilm-embedded bacteria, honey becomes less effective, and a high concentration of a honey solution is needed to eradicate the bacteria within the biofilm. To facilitate improvements in the antibacterial efficacy of honey, particularly against bacterial biofilms, honey has been supplemented with several distinct substances, including antimicrobial peptides [15], bacteriophages [26,27], and essential oils [17]. In the present study, we showed that supplementation of different types of honey with sub-MICs of Vit C resulted in a significant enhancement of the antibacterial activity against P. aeruginosa and E. coli.…”
Section: Discussionmentioning
confidence: 51%
“…In the case of biofilm-embedded bacteria, honey becomes less effective, and a high concentration of a honey solution is needed to eradicate the bacteria within the biofilm. To facilitate improvements in the antibacterial efficacy of honey, particularly against bacterial biofilms, honey has been supplemented with several distinct substances, including antimicrobial peptides [15], bacteriophages [26,27], and essential oils [17]. In the present study, we showed that supplementation of different types of honey with sub-MICs of Vit C resulted in a significant enhancement of the antibacterial activity against P. aeruginosa and E. coli.…”
Section: Discussionmentioning
confidence: 51%
“…Bacteriophages (phages) have regained interest as promising therapeutic option in fighting biofilmrelated infections due to their rapid bactericidal activity, the self-amplification ability and potential biofilm degradative properties (Harper et al, 2014). However, there are only limited studies investigating the activity of phages against polymicrobial biofilms (Sillankorva et al, 2010;Kay et al, 2011;Chhibber et al, 2015;Oliveira et al, 2018;Melo et al, 2019) and just recently Akturk et al (2019) evaluated the simultaneous and staggered administration of a P. aeruginosa-targeting monophage and conventional antibiotics on S. aureus/P. aeruginosa dualspecies biofilms.…”
mentioning
confidence: 99%
“…In this model, the phage challenge was significantly more effective than in an in vitro model. A previous study by Oliveira et al [122] showed that phages and chestnut honey action against biofilms formed in non-damaged porcine skin explants (which closely mimicked scratch wounds) increased with time against E. coli and P. aeruginosa mono and dual-species biofilms. The combined therapy resulted in bacterial reductions that were more effective on E. coli than on P. aeruginosa biofilms.…”
Section: Phage Therapy For Chronic Wound Healing-ex Vivo and Animal Imentioning
confidence: 97%